Literature and Contemporary Ideological Issues (Revue El-Wahat pour les Recherches et les Etudes, 2025)
Literature's textual compositions (linguistics and semantics) extend beyond the poetics that structuralist criticism has primarily explored. Rather, ideological frameworks shape it as a creative product, influencing both its explicit and implicit meanings. Therefore, this study aims to explore the relationship between literature and ideology, revealing that a literary work can encompass various human experiences and ideological orientations. As such, literature cannot be seen as an entirely individual creative practice nor a purely ideological process. Instead, it is the reconfiguration of the creator's experience and ideology in a new form, which we call the literary work. Consequently, the literary work is a reproduction of ideology, not its creation. Literature is a manifestation of ideology and one of its fields.Keywords: Ideology, Literature, Issues, Thought, Contemporary Ideology